진단용 방사선발생장치 이용에 적용되는 법제의 비교 - 고종경(Jong-Kyung Ko); 전여령(Yeo-Ryeong Jeon); 한은옥(Eun-Ok Han); 조평곤(Pyong -Kon Cho); 김용민(Yong-Min Kim) (방사선기술과학, 2015)
Diagnostic radiation devices that is used in the country has reached to 78,000 units. When used for human subjects diagnostic purposes, it is subject to Medical Service Act, when used in diagnostic purposes in animal subjects, the subject to Veterinarians Act. When used for other purposes are subject to the Nuclear Safety Act. Even the same radiation devices varies the legislation that is applied depending on the intended use and object. Diversified been p rovisions a re necessary compared to t he analysis o f l egal content in o rder t o prevent confusion of the legislation is a matter to be applied. It is a qualitative study that Nuclear Safety Act, Medical Service Act and Veterinarians Act administrative procedures for the introduction of the applied diagnostic radiation devices, safety inspection, human resources management, area management and the content related to administrative punishment. The Nuclear Safety Act sub-provisions, the introduction of diagnostic radiation generating devices, there are many complex and complete requirements administrative procedures on the concept of a permit. Inspection of safety associated with the use, would be subject to periodic inspection auditing characteristics over the entire field of radiation safety management. It must receive court regular education for the safety administrator and workers. Unlike the reference of the radiation dose rate to specify the radiation controlled area there is a measurement obligation of radiation dose rate. Unlike the reference of the radiation dose rate to specify the radiation controlled area there is a measurement obligation of radiation dose rate. Quantitative difference of administrative punishment that is imposed when legislation violation has reached up to 10 times, over the entire field, the largest burden of radiation safety management at the time of application of the Nuclear Safety Act sub provisions. And it is applied differently depending on the purpose and the imaging target using the same diagnostic radiation devices. Depending on the use mainly under the current legal system, radiation can be lacking in fairness of the contents of the legislation for safety management, there is a risk of confusion. Alternatives such as centralized and standardization of legislation by diagnostic radiation devices use is expected to be necessary. 국내에 사용되고 있는 진단용 방사선발생장치는 78,000여대에 이르고 있다. 인체 대상의 진단 목적으로 사용할 때에는 의료법의 적용을 받고, 동물 대상의 진단 목적으로 사용할 때는 수의사법의 적용을 받는다. 그 이외의 목적으로 사용 시에는 원자력안전법의 적용을 받는다. 동일한 방사선발생장치라도 사용목적 및 대상에 따라 적용되는 법제가 달라지며, 다원화된 규정이 적용되는 문제점인 법제의 혼란을 방지하기 위해 법제 내용의 분석 및 비교가 필요하다. 본 연구는 질적 조사로, 원자력안전 법, 의료법, 수의사법과 그 하위 규정에 적용되는 진단용 방사선발생장치 도입에 대한 행정절차, 안전성 검사, 인력 관리, 구역 관리, 행정처분에 관한 내용이다. 원자력안전법 하위규정에서는 진단용 방사선발생장치 도입은 허가개념으로 행정절차가 복잡하고 구비요건이 많다. 사용에 따른 안전성 검사는 방사선안전관리 전 분야에 걸쳐 감사 성격의 정기검사를 받게 된다. 안전관리자 및 종사자에 대해 해마다 법정 정기 교육을 받아야 한다. 방사선관리구역을 지정하는 방사선량률 기준이 다르며 방사선량률 측정 의무가 있다. 법제 위반 시 부과되는 행정처분의 양적 차이가 최대 10배에 이르며 전 분야에 걸쳐 원자력안전법 하위규정 적용 시 방사선안전관리 부담이 가장 크다. 동일한 진단용 방사선발생장치의 사용 목적과 촬영대상에 따라 다르게 적용되고 있는 현행 법 제도 하에서는 사용주체에 따라 방사선 안전관리를 위한 법제 내용의 형평성이 결여되어 있고, 혼란의 우려가 있으므로 진단용 방사선발생장치 이용에 따른 법제의 일원화 또는 표준화 등의 대안이 필요할 것으로 예상된다.